PEMANFAATAN POJOK BACA UNTUK MENINGKATKAN MINAT BACA SISWA DI SD NEGERI 1 MENANGA - Seniani, Ni Wayan; Numertayasa, I Wayan; Sudirman, I Nyoman (STKIP Suar Bangli, 2023)
This study aims to describe interest in reading in class IV SD Negeri 1 Menanga by using the reading corner. This type of research is descriptive qualitative. Collecting data with the method of observation, interviews, questionnaires and documentation. As for data analysis, namely data reduction, data exposure and verification. The subjects of this study were school principals, guardian teachers, Hindu religious teachers and fourth grade students. The results of the study show that there are 3 stages in planning a reading corner at SD Negeri 1 Menanga, namely first holding a meeting with the board of teachers regarding the existence of a reading corner program in each classroom. The two stages of storybook procurement planning are budgeted at the Bos Fund. The three implementation stages carried out literacy activities 15 minutes before the learning activities began. Furthermore, the reading corner at SD Negeri 1 Menanga is used as follows: firstly as material for School Literacy Movement (GLS) activities, secondly as reference material and material for discussion, and thirdly as material to fill students' free time. Based on the use of the reading corner at SD Negeri 1 Menanga, it really helps to increase students' interest in reading, especially in grade IV. The obstacles faced by teachers in using the reading corner at SD Negeri 1 Menanga are the minimal collection of story books and the lack of student initiative in reading books in the reading corner. corner at SD Negeri 1 Menanga, it really helps to increase students' interest in reading, especially in grade IV. (3) The obstacles faced by teachers in using the reading corner at SD Negeri 1 Menanga were the minimal collection of story books and the lack of student initiative in reading books in the reading corner.